A Study the Effect of TiO2 Nanoparticles Combination with Antibiotics and Plant extracts Against Some Gram Negative Bacteria (Baghdad Science Journal, 2016)
Titanium dioxide TiO2 has been widely utilized in cleaning and sterilizing material for many clinical tools sanitary ware, food tableware and cooking and items for use in hospitals. Titanium dioxide TiO2 non toxicity and long term physical and chemical stability. It has been widely used decomposition of organic compounds and microbial organisms such as cancer cell, viruses and bacteria as well as its potential application in sterilization of medical devices. The aim of the study the effect of titanium dioxide TiO2 on some Gram negative bacteria and study their effects on some virulence factors and chromosomal DNA.In this study, we obtained (E. coli ? Proteus mirabilis, Proteus vulgaris ? Pseudomonas aeruginosa ? Klebsiella pneumonia and Acinetobacter baumannii) from Al-Emamain Al-Kadhemain Medical City Hospital in Baghdad. Samples collection were carried out from 1 April to 30 June 2014. Study the effect of (plant extraction and Antibiotic) alone and combination with Titanium dioxide TiO2 on bacteria growth. And study the effect of Titanium dioxide TiO2 on biofilm layer and chromosomal DNA.Combinations of TiO2 nanoparticle with water and alcohol extracts of plant (Salvia officinalis ?Arctium minus, Origanum majorana and Anabasis syriaca) gave synergistic results against the gram negative bacterial isolates.A Synergism effect was observed in combination of Ciprofloxacin with Titanium TiO2 nanoparticles toward all Gram negative bacteria. Also a high efficiency was observed when TiO2 nanoparticles mixed with Amikacin toward all isolates except Acinetobacter baumannii and E. coli3. While the results of mixing TiO2 nanoparticles with Cephalothin indicate highly efficiency toward all isolates except Pseudomonas aeruginosa.The combination of plant extracts (Salvia officinalis ? Arctium minus ? Origanum majorana and Anabasis syriaca) with TiO2 nanoparticles was appear to be damaged to E. coli chromosomal DNA.The study showed the ability of nanoparticles TiO2 to inhibition of the layer Biofilm to all isolates of bacteria at concentrations (1, 1.5) µg/ ml.Conclude from this study we can be used TiO2 nanoparticles to kill some types of bacteria